The Importance of Interaction Between Nature and Society - Jobborova Gulnoza Kadamovna (European Science Publishing, 2023)
This article shows the results of the study, the uniqueness of pedagogical methods in the formation of a positive attitude to the environment among primary school students, as well as recommendations for the formation of a positive attitude to the necessary environment among primary school students. Environmental education is approved by students in educational institutions, increasing the sense of respect for nature and the environment in them, a careful attitude and a sense of responsibility, issues related to the environmental education of Primary School students, historical and ethnographic materials, ancestors. Environmental conditions were consistently studied by them, knowledge and experience in this regard were developed and aimed at forming the foundations of a deepened ecological culture.
Keywords: Man, anthropogenesis, society, socium, natural factors, natural environment, environment, nature.